Penerapan Metode MOORA untuk Optimalisasi Pemilihan Ketua Jemaat Gereja dengan Kriteria Berbasis Penilaian Objektif - Lumingkewas, Edwin; Tangka, George Morris William (Journal of Computer System and Informatics (JoSYC), 2024)
This study aims to support an objective and transparent selection process for church leadership within the Seventh-day Adventist Church (SDA), recognizing the importance of balanced spiritual and administrative leadership. To achieve this, the study applies the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method as a systematic approach, enabling a more objective, criteria-based candidate selection. MOORA is used to provide an evaluation model that combines criteria weighting and normalization, aiming to produce fairer and more measurable decisions compared to conventional methods. The analyzed criteria include spiritual maturity, community involvement, leadership experience, and doctrinal knowledge. The results show that applying MOORA increased the selection objectivity by 15% compared to previous methods, with candidate a3 achieving the highest score of 0.5708, followed by a1 (0.5663) and a2 (0.5589). By prioritizing criteria reflecting the church’s values, essential aspects such as spiritual maturity and community involvement receive greater emphasis. These findings demonstrate that MOORA supports faith-based decision-making aligned with church values, providing improved governance and applicability in other religious organizations facing similar selection challenges.